Batch investigation of constructed wetland microbial fuel cell with reverse osmosis (RO) concentrate and wastewater mix as substrate. (March 2019) - Das, Bhaskar; Thakur, Somil; Chaithanya, M. Sai; Biswas, Pinakpani
Abstract: In the present study we have integrated Microbial Fuel Cell with Constructed Wetland (CW) to evaluate its potential to remove Chemical Oxygen Demand (COD) and Total Dissolved Solid (TDS) along with electricity generation from the mixture (1:1) of domestic wastewater (WW) and reverse osmosis (RO) concentrate. Two vertical flow CW-MFCs have been investigated (with plant and without plant) in batch mode for 69 days. The plant species Canana India has been used for its suitability to sustain saline environment. The COD and TDS mass balance is studied for different organic loading and the result is compared with their removal efficiencies and electricity generation in the lab scale microcosms. The result shows that CW-MFC with plant (CW-MFC-1) and CW-MFC without plant (CW-MFC-2) produced maximum cell voltage of 0.86 V and 0.75 V respectively with COD removal of 88.1% and 83.1% and TDS removal of 82.05% and 77.5%. The maximum Normalized Energy Recovery (NER) values in CW-MFC-1 (NERs = 6.415 Wh kg −1 COD and NERv = 1.124 Wh m- 3 ) was also found more than CW-MFC-2 while maximum Columbic Efficiency (CE) was observed in CW-MFC-2 (C.E. = 1.9%). Enrichment of the nutrient from the RO concentrate positively influenced the performance of the CW-MFC with plant synergistically. Graphical abstract: Image 1 Highlights: CW-MFC using domestic wastewater and Reverse Osmosis (RO) concentrate. Salt tolerant plant species Canana Indica is used for optimal TDS and COD removal. Wastewater treatment and power generation in CW-MFC with plant and without plant. CW-MFC with plant shows better result in COD/TDS removal, Columbic efficiency and power generation. The Normalized Energy Recovery (NER) is more in setup with plant. .